CAPBLAT: An Innovative Computer-Assisted Assessment for Problem-Based Learning Approach - Muhammad Qomaruddin; Azizah Abdul Rahman; Noorminshah A. Iahad (Universitas Ahmad Dahlan, 2014)
This paper profiles the potential of developing and implementing Computer-Assisted Assessments (CAA) for helping lecturer in assessing students’ achievements on the Problem-Based Learning (PBL) Approach. PBL Assessment is typically formative; it includes delivery of feedback to the student, with the aim of improving their skills. The use of CAA in PBL gives advantages for both of lecturer and students by providing them with detailed formative feedback on their learning achievements compare to conventional assessment. It also reduces lectures tedious load by automating parts of the task of marking students’ work. The methodology applied to this research was literature review and investigation of practitioners’ perception about assessment in PBL. The literatures showed that there are methods of assessments that have been used successfully in PBL, but the research selected five methods as PBL assessment framework; there are “Peer-assessment, Self-assessment, Group presentation, Individual activities, and Group report assessment”. The framework applied into the tool that encompasses the use of computer (called with CAPBLAT) for helping lecturer in assessing students’ achievements. In addition, the CAPBLAT helps to store assessment material, deliver assessment, and do auto-rating of the assessment result. The evaluation results concerning technology acceptance demonstrated that incorporating CAPBLAT can get better technology acceptance.